PENGARUH LAMA PERENDAMAN DAUN SIRIH (Piper betle Linn.) DALAM MENJAGA KUALITAS BENIH SENGON (Paraserianthes falcataria (L.) Nielsen) - Tumela, Gallery; Mardhiansyah, M.; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Paraserianthes falcataria (L.) Nielsen is a fast-growing plant species that has been widely recognized by society in the development of forest plantations. Paraserianthes falcataria (L.) Nielsen has many uses ranging from leaves, stems to the roots. People generally just let the Paraserianthes falcataria (L.) Nielsen seeds grow naturally without making the treatment of the seeds. Seed treatment is by using plants that contain a disinfectant or antiseptic, and easily found around the neighborhood, including the Piper betle Linn. plant. This research aimed to determine the effect of soaking Piper betle Linn. leaves on the quality of the seed and determine the length of immersion Piper betle Linn. leaf which is optimal to protect seed quality. The research was compiled in a completely randomized design (CRD) with 5 treatments and 4 replications. The treatment consisted of soaking Paraserianthes falcataria (L.) Nielsen seeds with water immersion of Piper betle Linn. leaves for 10 minutes, 20 minutes, 30 minutes, 40 minutes and 50 minutes. Data were analyzed by analysis of variance using SAS 9.1.3 Portable. And than, continued with DNMRT double distance test at 5% level. The research results showed that the duration of Piper betle Linn. leaf soaking has an effect on seed germination and improve the quality of seeds during storage. The optimal time for Piper betle Linn. leaf soaking is 30 minutes with germination percentage of 86.00%, germination speed of 2.73 days and seed germination time of 8 days.Â Keywords: Paraserianthes falcataria (L.) Nielsen, Piper betle Linn., Seed Quality